Branding and Online Cataloging of CV. Galaxy Stone - Marcellina Carissa Santosa; Aristarchus Pranayama; Ryan P. Sutanto (k@ta: A Biannual Publication on the Study of Languange and Literature, 2023)
Galaxy Stone is a company that is engaged in the craft of various products made from natural stones with the main product, washbasin. When a pandemic happens, the interest in washbasin increase. At the same time, many target audiences still did not know about Galaxy Stone, which caused a lack of trust from the target audience. Also, the target audience feels difficulties when looking at the Galaxy Stone catalog because they did not know the differences between every product. To solve the problems above, branding needs to be made to build the brand image as a store that sells customizable interior products to provide customer comfort. Also, a catalog website that contains products catalog with comparison features is needed. Before making this design, several methods were used to collect data, namely observation, questionnaire, interviews, documentation, and literature studies. The concept in the design is minimalist so the brand looks elegant and luxurious. The media that are used in this design are stationary, social media, website, and marketplace. Hopefully, through the branding design and online catalog, the brand will get the target audience’s trust and more easily view the Galaxy Stone product catalog.